The Impact of Competence on Job Satisfaction and Performance: Moderating Effects of Work Environment, Motivation, and Digital Adoption - Iwan Budiherwanto; Tri Nur Rohmah (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Enhancing employee performance within the education sector has gained significance due to rising professional expectations and the rapid pace of digital transformation. Employee skills are viewed as a crucial element in improving job satisfaction and employee performance; nevertheless, their influence may differ based on organizational circumstances. This research intends to explore the effect of competence on job satisfaction and employee performance while considering work environment, motivation, and digitalization adoption as moderating factors. The study was carried out with all personnel from public junior high schools, comprising a total population of 384 participants. Primary data were gathered via an online questionnaire, resulting in a response rate of 76.6%. The analysis of the data was performed using linear regression and Moderated Regression Analysis (MRA). The results show that competence greatly influences job satisfaction, both directly and as influenced by the work environment. In addition, competence greatly enhances employee performance, and this impact intensifies with increased motivation and digitalization adoption. This research finds that adopting digital tools in education significantly enhances employee performance and can serve as a strategy for gaining a competitive advantage.